Sahara - Cussler, Clive (London HarperCollins Publisher, 2012)
Can Dirk Pitt tie past disappearances together while searching the Nile for a pharaoh's funeral barge?
Keywords: Pitt, Dirk (Fictitious character) -- Pollution -- Sahara